Caracterização e seleção de aços para molas helicoidais em sistemas de alimentação avícola - Roso, William Spenassato (2025)
The growth of poultry farming and the increasing demand for chicken meat have made the efficiency of helical conveyors for animal feeding essential to ensure productivity and quality. In this context, the helical conveyor spring plays a fundamental role but presents recurring wear issues. Therefore, this study aimed to select appropriate steels for the manufacturing of helical conveyor springs, with the objective of mitigating the wear problem initially identified through excessive vibration in the feeder lines. Quality management tools such as Plan-Do-Check-Act (PDCA) and Failure Modes and Effects Analysis (FMEA) were applied, along with tests to determine the mechanical properties of steels: SAE 1065 cold-rolled (lf), SAE 1070 cold-rolled (lf), SAE 1080 cold-rolled (lf), SAE 1065 high-pressure cold-rolled (lf-AP), and SAE 1030 heat-treated (tt). The analyses revealed that the wear was related to variations in raw materials, especially in the years 2017 and 2023, during which the chemical compositions of SAE 1065lf and SAE 1065lf-AP showed elevated levels of manganese, phosphorus, and sulfur, exceeding normative limits. Materials with hardness between 36 and 39 HRC, yield torque below 28 N·m, and elastic constants above 14 Kgf/mm, combined with dimensional changes, demonstrated unsatisfactory performance, showing wear of up to 0.58 mm, approximately 7.73% of the original wire width (7.5 mm) within the first 12 months of operation. On the other hand, materials with hardness between 39 and 42 HRC, yield torque between 28 and 33 N·m, and elastic constants ranging from 10 to 14 Kgf/mm exhibited better performance, especially SAE 1030tt, which showed no measurable wear and offered a 21.28% reduction in material cost. The DFMEA analysis of field assembly revealed that improper stretching of the spring contributes to accelerated wear, recommending a stretch between 1 and 1.5% at each end. Improper management, such as increased feed density and partially filled lines, also intensifies torsional stress and promotes premature wear. Thus, it is recommended to review the spring stretching during downtime and use lower-density feed, ensuring that the lines are fully filled. The combination of appropriate mechanical properties, correct assembly, and proper management ensures greater durability and efficiency of the poultry helical conveyor system.